2021
DOI: 10.1093/femsmc/xtab021
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characteristics of bacteremias among COVID-19 hospitalized patients in a tertiary referral hospital in Northern Greece during the second epidemic wave

Abstract: Northern Greece was struck by an intense second COVID-19 epidemic wave during the fall of 2020. Because of the coinciding silent epidemic of MDR organisms the handling of COVID-19 patients became even more challenging. In the present study, the microbiological characteristics of bacteraemias in confirmed cases of hospitalized COVID-19 patients were determined. Data from 1165 patients hospitalized between September and December 2020 were reviewed regarding the frequency of bloodstream infections, the epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
7
17
0
Order By: Relevance
“…As epidemiology of BSI in COVID-19 patients, similar to non-COVID-19 patients, varies among countries and continents, continuous surveillance is required [ 12 ]. Our study demonstrated high rates of MDR pathogens, as also reported from another hospital in our country [ 20 ]; both studies mirror the endemic spread of MDRO, especially Gram-negatives. Protonotariou et al reported a higher rate of MDRO (58% vs. 46% in our study) possibly because ICU patients prevailed in that cohort.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As epidemiology of BSI in COVID-19 patients, similar to non-COVID-19 patients, varies among countries and continents, continuous surveillance is required [ 12 ]. Our study demonstrated high rates of MDR pathogens, as also reported from another hospital in our country [ 20 ]; both studies mirror the endemic spread of MDRO, especially Gram-negatives. Protonotariou et al reported a higher rate of MDRO (58% vs. 46% in our study) possibly because ICU patients prevailed in that cohort.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of BSI in COVID-19 patients and their outcome has been studied mostly in ICU or in mixed populations of both ICU and medical wards [ 11 ]. Furthermore, epidemiology of bacterial and fungal pathogens in BSI of patients with COVID-19 was mostly described in ICU departments with endemicity of multidrug antimicrobial resistance, but not in non-ICU COVID-19 settings [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, systematic reviews and metanalyses have evaluated prevalence, microbiological characteristics, clinical course and outcomes of secondary infections in patients hospitalized with COVID-19 (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…have severely affected the treatment of patients admitted in ICUs 1 – 3 . Multidrug-resistant A. baumannii was one of the most frequent pathogens isolated from patients hospitalized in the ICU for severe COVID-19 pneumonia 4 or bacteremia 5 . In 2021, the World Health Organization (WHO) introduced antibacterial vaccines as an effective tool to reduce antibiotic resistance 6 .…”
Section: Introductionmentioning
confidence: 99%